An experimental study on spontaneous recovery of conditioned reward expectancies and instrumental responding in humans - Steins-Löber, Sabine; Madjarova, Radka; Lörsch, Frank; Herpertz, Sabine; Flor, Herta; Duka, Theodora (Behaviour research and therapy, 2019)
The aim of the present study was to investigate spontaneous recovery of reward-expectancies and a reward-associated response in humans and to assess individual factors affecting spontaneous recovery. We therefore implemented an experimental procedure comprising three separate test-sessions. In the first test-session, participants underwent instrumental discrimination training to acquire a conditioned reward-associated response, in the second test-session, memory of this response was tested followed by extinction training. In the third test-session, extinction memory was assessed. Our results demonstrate spontaneous recovery of extinguished conditioned reward-associated expectancies and indicate that differential expectancies after training and extinction and impulsivity significantly predicted the magnitude of spontaneous recovery. In contrast, limited evidence for spontaneous recovery of instrumental responding was found. Given that reward-expectancies might trigger instrumental responding these findings underline the importance of developing extinction procedures that lead to more complete and less fragile long-term extinction of reward-associated responses.